2007
DOI: 10.2174/138955707779802624
|View full text |Cite
|
Sign up to set email alerts
|

myo-Inositol Monophosphatase: A Challenging Target for Mood Stabilising Drugs

Abstract: myo-Inositol monophosphatase has long been a target for drug discovery. Recent work has given detailed insight into its mechanism and dynamics plus new activities and some novel series of inhibitors. The goal of a bio-available inhibitor for this enzyme, however, remains a major challenge for medicinal chemistry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 31 publications
0
6
0
Order By: Relevance
“…These proteins contain conserved synaptojanin‐like IMPase domains and are predicted to be targeted to the cytoplasm (PF3D7_0705500) or intracellular membranes (PF3D7_0802500) respectively. Cytosolic and membrane‐bound forms of IMPase are also predicted to occur in other organisms (Vadnal et al ., ; Miller and Allemann, ). Whether these proteins have redundant functions in myo ‐inositol synthesis or are involved in channelling different pools of myo ‐inositol to the ER or Golgi‐located PI synthase remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…These proteins contain conserved synaptojanin‐like IMPase domains and are predicted to be targeted to the cytoplasm (PF3D7_0705500) or intracellular membranes (PF3D7_0802500) respectively. Cytosolic and membrane‐bound forms of IMPase are also predicted to occur in other organisms (Vadnal et al ., ; Miller and Allemann, ). Whether these proteins have redundant functions in myo ‐inositol synthesis or are involved in channelling different pools of myo ‐inositol to the ER or Golgi‐located PI synthase remains to be determined.…”
Section: Discussionmentioning
confidence: 99%
“…Both agents were poorly bioavailable, although recent in vivo studies found lithium‐like effects of high systemic doses of L690330 in mice (Atack et al, ; Shtein et al, ). Other than this advance, progress in the development of IMPase inhibitors has been limited (Miller and Allemann, ). In a recent drug‐repurposing study, we identified the antioxidant agent ebselen as a brain‐penetrant IMPase inhibitor (Singh et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…Then, it was discovered that low millimolar concentrations of Li + inhibit IMPase-catalysed dephosphorylation of myo -inositol-1-phosphate [ 1 ], which could plausibly explain the marked decrease of myo -inositol in brain tissue following administration of lithium, a veteran therapeutic in manic depression treatment [ 2 ]. Inhibition of myo -inositol synthesis affects the phosphatidyl inositol second messenger pathway, which is linked to manic depression, and it is now widely accepted, though unproven, that IMPases constitute a major target of lithium therapy [ 3 ].…”
Section: Introductionmentioning
confidence: 99%